Inactivation of KAT1 channel of guard cells at submillimolar concentrations of external potassium - Horváth, Ferenc (Acta Biologica Szegediensis, 2005)
In the present study we investigated the effect of depleting K+o on the activity of a plant K+ channel, the inward rectifier KAT1 from Arabidopsis thaliana. Most voltage sensitive K+ channels are able to sense the concentration of extracellular K+ (K+o) and inactivate if K+o decreases to sublillimolar values. The channel was expressed in mammalian HEK293 cells and measured with patch clamp in the whole cell configuration. The effect of K+o depletion on channel activity was monitored from the tail currents before during and after washing K+o from the medium. The data show that a depletion of K+o results in a decrease in channel conductance. This high sensitivity of the channel to K+o could serve as a safety mechanism, which inactivates the channel at low K+o and prevents in this way leakage of K+ from the cells via this type of channel.